Comparison of different fiber post systems using push-out bond strength test - Hani M. Mouafaq; Shakhawan K. Kadir (Erbil Dental Journal)
Background and Objective: Nowadays, the use of fiber post in weak teeth that had root canal treatment has gained acceptance worldwide. New materials and shapes of fiber posts were introduced. This study was conducted to compare in vitro bond strength among Bundle glass fiber posts, taper glass fiber post and short fiberreinforced composite as post material.